2008
DOI: 10.1016/j.jconrel.2008.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Fast degrading polyesters as siRNA nano-carriers for pulmonary gene therapy

Abstract: A potential siRNA carrier for pulmonary gene delivery was assessed by encapsulating siRNA into biodegradable polyester nanoparticles consisting of tertiary-amine-modified polyvinyl alcohol (PVA) backbones grafted to poly(d,l-lactide-co-glycolide) (PLGA). The resulting siRNA nanoparticles were prepared using a solvent displacement method that offers the advantage of forming small nanoparticles without using shear forces. The nanoparticles were characterized with regard to particle size, zeta-potential, and degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
89
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 46 publications
(55 reference statements)
1
89
0
Order By: Relevance
“…The use of polymeric nanoparticle systems for drug and vaccine delivery offers several advantages, including controlled delivery of encapsulated payload(s) and, depending on their chemical properties, improved biocompatibility, receptor targeting capabilities, sustained antigen/drug release kinetics, adjuvanticity, and opportunities for both local and systemic delivery (12,13). Polyanhydride nanoparticles have displayed these characteristics in both in vitro and/or in vivo settings (6,9,(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The use of polymeric nanoparticle systems for drug and vaccine delivery offers several advantages, including controlled delivery of encapsulated payload(s) and, depending on their chemical properties, improved biocompatibility, receptor targeting capabilities, sustained antigen/drug release kinetics, adjuvanticity, and opportunities for both local and systemic delivery (12,13). Polyanhydride nanoparticles have displayed these characteristics in both in vitro and/or in vivo settings (6,9,(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several different DDS have been developed for inhalation delivery of different drugs. Liposomes (10-13), lipid-and polymerbased nanoparticles (14)(15)(16)(17), are the most frequently used carriers for local pulmonary delivery of different drugs, antisense oligonucleotides (ASO), and short-interfering RNA (siRNA).…”
mentioning
confidence: 99%
“…Previous work carried out by us demonstrated that microparticles of 2.1 µm in size were optimal for cell uptake in primary alveolar macrophages and differentiated THP-1 cells, and can be further enhanced through coating with gelatin [120]. For efficient pulmonary delivery the optimum mass median aerodynamic diameter (MMAD) of particles ranges between 1 µm to 5 µm that can be achieved using a range of manufacturing processes for PLGA microparticles [121]. Whilst size can be optimized through variations in manufacturing, encapsulation efficiency for siRNA in PLGA microparticles is poor.…”
Section: Microparticles For Targeting Amsmentioning
confidence: 99%